Effect of Strawberry Powder Substitution on the Organoleptic of Instant Pudding : Pengaruh Substitusi Bubuk Stroberi terhadap Karakteristik Puding Instan - Mia Srimiati; Putri Habibah; Annisa Dinya Zahra; Febry Harsanti; Alfisa R Ratu Maharani (Media Gizi Indonesia, 2023)
Strawberries are a nutrient-dense fresh fruit, but their use is restricted and they are quickly damaged due to their high water content. Therefore, innovation in strawberry processing is required so that the range of strawberry-processed goods is wider and has a longer shelf life, such as instant pudding. This study examined the effects of substituting strawberry powder to produce instant pudding with the highest nutritional and organoleptic qualities. The experimental design of the study includes four treatments, F1 (2%), F2 (4%), F3 (6%), F4 (8%), and F0, each of which contains a different dose of strawberry powder (control). The research was conducted at the Saraswati Indo Genetech laboratory in Bogor and the culinary and dietetics laboratory at Binawan University. Using Microsoft Excel 2019 and SPSS, the normality test (Kolmogorov Smirnov) and the Kruskal-Wallis test were applied to the organoleptic test results data. The results of the Kruskal Wallis test indicated a significant effect; the Mann-Whitney test was then conducted. The results revealed that instant pudding significantly altered color, flavor, texture, and odor. The most popular product is the F4 formulation, which contains 8% strawberry powder. The instant pudding has a water content of 75,62%, an ash content of 0,72%, protein content of 2,84%, a fat content of 1,25%, and carbohydrate content of 19,56%, according to an approximate analysis. It was impossible to determine the vitamin C content of the instant pudding because it was not recognizable.